Empowering Learning: Simple Tool Practicum-Based POE Model for Student Outcomes: Meningkatkan Hasil Belajar Siswa melalui Model Pembelajaran POE Berbasis Praktikum Alat Sederhana - Mega Resida; Noly Shofiyah (Academia Open, 2023)
This pre-experimental quantitative study aimed to investigate the impact of a POE (Predict, Observe, Explain) learning model based on a simple tool practicum on student learning outcomes. The research was conducted at SMP Negeri 2 Gedangan, with one experimental class and two replication classes. Non-probability random sampling was employed to select the participants. The assessment instrument consisted of multiple-choice questions to measure learning outcomes. Data analysis included the N-Gain test and paired sample t-test. The findings revealed that the N-Gain scores for all three classes were in the moderate category, and the paired sample t-test showed a significant increase in learning outcomes (p < 0.05) in each class. The results suggest that implementing the simple tool practicum-based POE learning model positively influences student learning outcomes. This study contributes to the field of education by highlighting an effective approach to enhance student learning through hands-on experiences and the application of the POE model. Highlights: The study focuses on enhancing student learning outcomes through a POE learning model and a simple tool practicum. The research employs a quantitative approach, utilizing the N-Gain test to assess the effectiveness of the intervention. The findings demonstrate a significant improvement in student learning outcomes, highlighting the potential of the simple tool practicum-based POE learning model. Keywords: Student learning outcomes, POE learning model, Simple tool practicum, Quantitative research, N-Gain test.